MODERN METHODS FOR ORGANIZING ENGLISH LANGUAGE TEACHING IN SCHOOLS BASED ON BLOOM’S TAXONOMY - Bobojonova I. Y. (European Science Publishing, 2024)
This article explores modern methods for organizing English language teaching in schools based on Bloom’s Taxonomy. It discusses how contemporary pedagogical approaches align with each level of Bloom’s Taxonomy, from remembering and understanding to applying, analyzing, evaluating, and creating. The article highlights practical methods such as role-playing, project-based learning, and the use of modern technologies to enhance English instruction. It emphasizes the importance of integrating these methods to improve students' cognitive skills and language proficiency effectively.
Keywords: Bloom’s Taxonomy, English language teaching, pedagogical methods, role-playing, project-based learning, modern technologies, cognitive skills.